Penerapan Metode Dempster Shafer Pada Sistem Pakar Diagnosa Penyakit Rabies - Juan Veron Christian L Sirait; Iqbal Kamil Siregar; Cecep Maulana (Universitas Budi Darma, 2022)
Rabies is a disease caused by the bite of animals such as dogs, cats and bats, if not treated quickly it can cause death. Patients can make a diagnosis for easy treatment of the disease. The number of patients who died because of the bites of animals that transmit Rabies. Animal owners still do not understand the consequences of the bites of the animals they maintain. Advances in expert systems can overcome this problem, namely by designing a web-based computer system that is integrated with databases and programming languages such as PHP-MySQL so that can help people with Rabies to diagnose the symptoms and types of the disease. The purpose of this research is to build an expert system to diagnose web-based Rabies. The application of the expert system in making this decision uses the Dempher Shaper method by generating true and false values on the new and old knowledge bases and comparing them with the weight values in each frame so that the percentage of the disease type is obtained. The result of the system implementation is that the system provides questions in the form of symptoms that must be answered by the patient based on the symptoms experienced by the patient and the results of the process the system will provide information on the type of Rabies Rabies (Prodromal Stage) = with a confidence value of 80.4% and can also obtain a solution.